Pierre Robin sequence and obstructive sleep apnea - Rubens Reimão; Elio Giacomo Papaiz; Luiz Fernando Papaiz (Arquivos de Neuro-Psiquiatria)
The case of a 12-year-old female patient with Pierre Robin sequence is reported, in which reduction of the pharyngeal airway leads to obstructive sleep apnea syndrome (OSAS) and excessive daytime sleepiness. Radiological evaluation, computerized tomography and magnetic resonance image showed bilateral temporomandibular ankylosis. Cephalometric data evidenced marked reduction of the posterior airway space. Three all-night polysomnographic evaluations detected severe OSAS with decrease in oxygen saturation. The Multiple Sleep Latency Test (MSLT) perfomed on two separate days objectively quantified the excessive daytime sleepiness with short sleep latencies; stage REM was not present. Polysomnography, MSLT and thorough radiologic studies, in this case, made it possible to determine the severity of OSAS, the site of obstruction, and the associated malformations.